PELATIHAN & PENGEMBANGAN APARATUR SIPIL NEGARA DALAM MENINGKATKAN KEMAMPUAN KERJA LINGKUNGAN DINAS KOPERASI, PERINDUSTRIAN, PERDAGANGAN DAN UMKM KOTA BATU - Sherly Najiwa Fitri (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
This research was conducted at the Department of Cooperatives, Industry, Commerce and Small and Medium Kota Batu in November 2016, involving 50 respondents. Of the 50 respondents were there, more than 50% were men, the majority of respondents have an educational background Bachelor of Tier One and most respondents obtain information on the effect of training, development, employability and motivation of personnel civil state from the Department of Cooperatives, Industry, trade and Small and Medium Enterprises Kota Batu. This study aims to determine the effect of training and development that directly affect work ability and motivation as intervening variables also affect work ability, motivation variable as an intervening variable. From the results of research conducted and calculations using path analysis produced that, training and development and motivational effect on work ability civil state apparatus of Cooperatives, Industry, Commerce and Small and Medium Kota Batu.